Climate change and sustainable development: Uncertainties and narratives - Stanley, Leonardo Ernesto (2024)
The current warming trend of our planet is extremely likely to be the result of human activity since the mid-20th century. Changes in the climate will become more and more recurrent, which will bring increasing economic problems. Transposing Earth's boundaries, on the other hand, might lead climate as well as nature to unknown territories where the non-knowledge prevails. How to make decisions in this context? Radical uncertainty forces us to make decisions "in the dark", where narratives help us to anticipate an explanation for unexplained events.